Dependence Structure between Conventional and Islamic Indexes: A Copula Approach - Messaoud, Samia Ben; Kouki, Mondher (International Journal of Islamic Banking and Finance Research, 2020)
This article examines the conditional dependence structure between Islamic stock indexes and conventional counterparts. Our empirical analysis relies on Islamic and conventional indexes of dependence distribution using copula methods over the period 1999–2014. The results from the copula models denote that the dependence is not formally symmetric in that the lower tail dependence is significantly larger than the upper tail dependence.